Signaling mechanisms of vasopressin/oxytocin-type neuropeptide-induced muscle contraction in the sea cucumber Apostichopus japonicus - Huachen Liu; Xiao Cong; Maurice R. Elphick; Muyan Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

MS-type neuropeptide function on locomotor behaviors and potential neuromodulation mechanism in a marine invertebrate Apostichopus japonicus - Yingqiu Zheng; Huachen Liu; Muyan Chen (Aquaculture, 2026)

Transcriptomic and metabolomic profiling of crown-of-thorns starfish planktonic larvae offers a comprehensive resource for identifying potential biocontrol targets - Yanlin Wang; Faraz Ali; Scott F. Cummins; Gang Ni; Muyan Chen (Coral Reefs, 2026)

Sea Cucumber Neuropeptides: Bridging Molecular Insights Towards Aquaculture Innovations - Yingqiu Zheng; Huachen Liu; Saowaros Suwansa‐ard; Scott F. Cummins; Muyan Chen (Reviews in Aquaculture, 2026)
The sea cucumber (class Holothuroidea) holds significant commercial value due to strong global demand, especially in East and Southeast Asian markets. Overexploitation of wild stocks has thus driven aquaculture expansion; however, current culture methods remain inadequate to meet projected demand or overcome traditional practice limitations. As evolutionarily ancient endogenous bioactive molecules, neuropeptides regulate diverse physiological processes and behaviors, demonstrating great potential as eco‐friendly tools for precision sea cucumber aquaculture. Identification and functional characterization of these neuropeptides improve our understanding of their evolutionary history and facilitate their application in aquaculture practice. In this review, we summarize the diversity of known sea cucumber neuropeptides and their receptors, their engagement with downstream cellular signaling pathways, and their roles in key biological processes, including feeding and growth, reproduction, regeneration, larvae settlement and metamorphosis, and locomotion. Future research should prioritize investigating neuropeptide regulatory networks, determining their functions across developmental stages, developing large‐scale peptide production methods, and improving delivery efficiency, all of which are critical for the application of neuropeptides to achieve sustainable, eco‐friendly sea cucumber aquaculture.

Multi-scenario assessment of living-wall effects on building air purification, noise attenuation, and thermal insulation using quantum machine learning - He Zhang; Ravi Srinivasan; Chen Chen; Xu Yang; Vikram Ganesan; Muyan Chen (Building and Environment, 2026)

Genome-wide DNA methylation profiling reveals epigenetic regulation of sex differentiation and gonadal development in Apostichopus japonicus - Yixin Wang; Xuemin Wang; Yanlin Wang; Muyan Chen (Aquaculture, 2026)

Development of high-efficiency spawning methods and gonadal stress responses in tropical sea cucumber Holothuria leucospilota - Yikun Cen; Yingqiu Zheng; Dejian Su; Dong Wang; Muyan Chen; Zonghe Yu (Aquaculture, 2026)

Solid-gas emission behavior of rubber powder modified asphalt: Component identification and suppression method - Jianwei Zhang; Meizhu Chen; Yansong Fan; Dongyu Chen; Muyan Han (Journal of Cleaner Production, 2025)

miRNA-mRNA interaction mechanism in echinoderm Apostichopus japonicus in response to acute hypoxia - Yanlin Wang; Yingqiu Zheng; Yingchao Yin; Lidong Sun; Muyan Chen (Aquaculture, 2025)

Feeding and growth are regulated by light and opsins-mediated phototransduction in sea cucumber Apostichopus japonicus - Lihua Liu; Xiao Cong; Xuemin Wang; Muyan Chen (Aquaculture, 2025)

Epiphytic mosses alter Pinus massoniana deadwood microbial and physicochemical properties thereby influencing the decomposition process - Bingyang Shi; Xiurong Wang; Shuoyuan Yang; Hongmei Chen; Yang Zhao; Qiao Liu; Rong Zou; Muyan Xie; Lixin Duan; Fang Liao (Plant and Soil, 2024)

Development and application of molecular markers in fisheries, aquaculture, and industry of representative temperate and tropical sea cucumbers: a review - Xinghai Liu; Xinyue Tang; Muyan Chen; Gang Ni; Yujia Yang (Frontiers in Marine Science, 2024)
Sea cucumber has emerged as a crucial economic species in aquaculture in China because of its remarkable nutritional and medicinal value. However, wild sea cucumber populations have experienced a decline due to overfishing and environmental factors, underscoring the urgent need for genetic resource conservation and biotechnology innovation within the sea cucumber aquaculture and breeding industry. The development of the sea cucumber industry is still impeded by challenges and difficulties. Nevertheless, significant progress has been made through the utilization of molecular markers, which have effectively addressed a number of fisheries and aquaculture issues. In recent years, diverse types of molecular markers including mitochondrial DNA, microsatellites, and SNP markers have been developed and extensively applied in various aspects of sea cucumber research. These markers play vital roles in genetic sex identification, germplasm resource evaluation, population structure assessment, as well as marker-assisted breeding in marine ranching and sea cucumber aquaculture and breeding industry. This review provides an overview of the fundamental principles, functions, and characteristics associated with various markers employed across various sea cucumber species while also discussing their applications within different aspects of the sea cucumber fisheries, aquaculture, and breeding industry.

A potential feeding regulation strategy during aestivation: Relaxation of intestine mediated by pedal peptide/orcokinin-type neuropeptides in sea cucumber Apostichopus japonicus - Yingqiu Zheng; Huachen Liu; Xiao Cong; Kenneth B. Storey; Muyan Chen (Aquaculture, 2024)

Characterization and expression profile of transient receptor potential channels in sea cucumber Apostichopus japonicus - Xuemin Wang; Yixin Wang; Yanlin Wang; Kenneth B. Storey; Muyan Chen (Frontiers in Marine Science, 2023)
Background In the past few decades, heat waves and seasonal variation linked with global warming are causing frequent fluctuations of water temperature in aquatic environments, resulting in further challenges for marine organisms. As a poikilothermic marine animal and a temperate species, sea cucumber A. japonicus is also very sensitive to temperature variation and shows a limited ability to adapt to environmental temperature changes. However, the molecular mechanisms by which A. japonicus perceives signals from such a diverse environment including the trigger of aestivation still remain unclear. TRP (transient receptor potential) superfamily, as the great potential “sentinel” of the organism in response to the changes of the external environment signals, perceived little attention and will be the future great candidates for sensory function research in echinoderm. Methods BLAST program was applied to identify the AjTRPs based on A. japonicus transcriptome database. Gene structure analysis of AjTRPs and phylogenetic analysis of TRPs were performed. The expression profiles of AjTRPs in different tissues and in response to different heat stress treatments (chronic/ acute) were measured using qRT-PCR. Results A total of 54 TRPs were identified in A. japonicus . Gene structure analysis showed that the exon numbers and the domains of AjTRPs varied greatly. Phylogenetic analysis indicated that AjTPRs were mainly grouped into six subfamilies: TRPA, TRPM, TRPC, TRPV, TRPML, and TRPP. Copy numbers of each TRP member in marine invertebrates including A. japonicus were more than those in vertebrates, however some TRP channel members were lost in invertebrates. Expression profile detection suggested that the representative 15 AjTRP genes belonging to 6 subfamilies were expressed in all tissues examined. Conclusion Our findings indicate that the plastic evolutionary history of TRP channel genes and suggest that TRPM2-1, TRPM2-2, TRPM3, and TRPC3-1 are potential thermo-TRP proteins involved in thermal regulation in A. japonicus . This work facilitates the knowledge of TRP-mediated sensory systems in echinoderms, provides new insights into the mechanisms of aestivation and global warming adaptation in marine invertebrates.

Metabolic response of the sea cucumber Apostichopus japonicus during the estivation-arousal cycles - Ye Zhao; Haona Wang; Han Wang; Yongrui Pi; Muyan Chen (Frontiers in Marine Science, 2022)
Estivation is a widespread survival strategy for dealing with adverse environmental conditions such as high temperature, low oxygen and lack of water or food, which has been reported across multiple vertebrate and invertebrate species. The sea cucumber Apostichopus japonicus is an excellent model organism to investigate the adaptive mechanism of estivation in marine invertebrates. In this study, a metabolomics approach based on ultraperformance liquid chromatography coupled with electrospray ionization time-of-flight mass spectrometry (UPLC-ESI-Q-TOF/MS) was performed to reveal the metabolic response of intestines from adult A. japonicus over the annual estivation-arousal cycle: nonestivation (NA), deep-estivation (DA) and arousal from estivation (AA). A total of 424 metabolites were identified, and among them, 243, 238 and 37 significant differentially metabolites (DMs) were further screened in the comparisons of DA vs. NA, AA vs. DA, and AA vs. NA. Specifically, the levels of metabolites involved in glycolysis and the tricarboxylic acid cycle were significantly decreased, while higher amounts of long-chain fatty acids, phospholipids and free amino acids were found in A. japonicus during estivation, implying that sea cucumbers might reorganize metabolic priorities for ATP production by depressing carbohydrate metabolism and promoting lipid and amino acid catabolism. Interestingly, elevated relative carbon flow entry into the pentose phosphate pathway and accumulation of various nonenzymatic antioxidant molecules (e.g., tocotrienols, folic acid, catechin, genistein and resveratrol) were observed in estivating sea cucumbers, which suggested that enhancement of the reactive oxygen species defense system might promote long-term viability in the hypometabolic state in an energy-efficient manner. Thus, this research provides new insights into the adaptation mechanisms of marine invertebrates to estivation at the metabolic level.

Structural and Functional Improvements of Coastal Ecosystem Based on Artificial Oyster Reef Construction in the Bohai Sea, China - Xu Wang; Jie Feng; Chenggang Lin; Hui Liu; Muyan Chen; Yunling Zhang (Frontiers in Marine Science, 2022)
Oyster reefs are gaining more and more attention in marine ranching and coastal ecosystem restoration, but tremendous knowledge gaps still exist. In this study, we developed trophic models for the established artificial oyster reef (EAOR), newly deployed artificial oyster reef (NAOR), and non-reef bare substratum (NBS) ecosystems located in the Bay of Xiangyun, Bohai Sea, China, to assess the benefits of artificial oyster reef construction and to characterize the unique role of these reefs in coastal management. The analysis showed that the EAOR and NAOR ecosystems were similar to each other, but both were greatly different than the NBS ecosystem. Reefs showed greater “ecological size” and stronger top-down effects compared to the bare area. The ecosystems were not yet mature, but the EAOR and NAOR ecosystems had more complicated trophic relationships, greater potential to withstand perturbations, and higher biological carrying capacities of commercial organisms compared to the NBS ecosystem. These results demonstrated that artificial oyster reef construction resulted in great advantages to the ecosystem. For example, oysters became the structuring functional group and played a critical role in the trophic structure of the reef areas. The phytoplankton/detritus-oysters-carnivorous macrobenthos pathway developed and became dominant in these areas, thereby contributing to highly efficient secondary production. The ratios of total primary production/total respiration were < 1, indicating that the reef ecosystems responded effectively to nutrient inputs from adjacent ecosystems. We speculate that water exchange might be a critical factor influencing the maintenance of the system. Long-term monitoring of the EAOR and NAOR should be implemented for oyster protection and to assess the need to manipulate carnivorous macrobenthos to keep the systems in balance. Results of this study could benefit the restoration, exploitation, and management of oyster reefs. Further studies should take the adjacent ecosystems and anthropogenic activities into account.

A Novel Full-Length Transcriptome Resource for Sea Cucumber Apostichopus japonicus Using Pacbio SMRT Sequencing - Yujia Yang; Muyan Chen; Yixin Wang; Lina Sun (Frontiers in Marine Science, 2022)

PacBio Isoform Sequencing and Illumina RNA Sequencing Provide Novel Insights on Responses to Acute Heat Stress in Apostichopus japonicus Coelomocytes - Yanlin Wang; Yingchao Yin; Xiao Cong; Kenneth B. Storey; Muyan Chen (Frontiers in Marine Science, 2022)
Significant increases in global sea surface temperatures are expected with climate change and may cause a serious challenge for marine organisms cultured in aquatic environments that are characterized by short and long-term fluctuations in water temperatures. Apostichopus japonicus , a sea cucumber with high nutritional value and pharmacological properties, is an important economic species that is widely raised in aquaculture in China. In recent years, continuous extreme high temperatures (up to 30°C) have occurred frequently in summer leading to mass mortality of sea cucumbers cultured in semi-open shallow regions seriously restricting the sustainable development of sea cucumber aquaculture. In the present study, we combined RNA-seq and PacBio single-molecular real-time (SMRT) sequencing technology to unveil the potential mechanisms of response to acute heat stress in A. japonicus coelomocytes. A total of 1,375 differentially expressed genes (DEGs) were identified in a comparison of control and 48 h heat stress (HS) groups. Pathway enrichment analysis indicated that nine important pathways induced by HS were significantly enriched ( q -value < 0.05) and mostly fell into four classes: folding, sorting, and degradation, immune and infectious diseases, signal transduction, and post-transcriptional regulation. Among them, all 41 genes connected with protein processing in endoplasmic reticulum were significantly up-regulated, and 12 of these were selected and validated via qPCR. Furthermore, changes in alternative splicing (AS) were also identified in sea cucumbers following HS. A total of 1,224 and 1,251 differential alternative splicing (DAS) events were identified using splice junction counts (JC only) and reads on target and junction counts (JCEC) as the input for rMATS in CO-HS comparison. We further found that the RNA splicing-related genes were enriched in the spliceosome pathway and showed DAS in control versus heat-stressed animals. In particular, we compared and confirmed that the hsfs1 gene, the master regulator of the heat shock response, showed differentially spliced exons in response to HS. This is the first comprehensive study showing that transcriptional and post-transcriptional (AS) controls are involved in the acute heat stress response of sea cucumber coelomocytes and provides novel insights into the molecular mechanisms of echinoderm adaptation to environmental stress.

Effects of Food Deprivation Duration on the Behavior and Metabolism of Black Rockfish (Sebastes schlegelii) - Fengyuan Shen; Zonghang Zhang; Yiqiu Fu; Zhen Zhang; Xin Sun; Jianyu Dong; Xiayang Ding; Muyan Chen; Xiumei Zhang (Fishes, 2021)
Fish often undergo food shortages in nature, especially for juveniles that are relatively vulnerable in most aspects. Therefore, the effects of food deprivation on fish behavior and physiology are worth exploring. Here, we investigated the behavioral and metabolic adaptations of the juvenile black rockfish Sebastes schlegelii to different durations of food deprivation. In this study, three treatments were set: control group, short-term food deprivation (STFD) group, and long-term food deprivation (LTFD) group. The rearing lasted for six weeks. During this period, videos were recorded three times per week to assess the locomotor activity and aggression. After this, the fishes’ boldness, neophobia, and aggressiveness were assessed using different behavioral assessment devices, while the standard metabolic rate (SMR) was measured by flow-type respirometry. In general, the values of the four indicators (swimming time, the number of turns, movement number, and attack number) for the STFD group were significantly higher than those for the control and LTFD group during the same period of rearing. In a subsequent personality assessment, the STFD group was observed to be significantly bolder in an assessment measuring boldness than the control and LTFD group (indicated by time in the circle, swimming time, number of times through the circle, and frequency in the circle). The LTFD group was observed to be more exploratory in the assessment of neophobia (indicated by duration in the exploratory area, distance from novelty item, and frequency of stay in the exploratory area). Indeed, the LTFD group was observed to be significantly less aggressive in the assessment of aggressiveness than the control and STFD group (indicated by attack number, attack range frequency, first attack, and winner). SMR was noted to be significantly higher in the STFD group than in the control and LTFD group. In conclusion, this study firstly reported the effects of food deprivation duration on the personalities of black rockfish, as well as the behavioral and physiological mechanisms. Thus, we hope to provide insights into the work of stock enhancement.

Ultrastructural variation and key ER chaperones response induced by heat stress in intestinal cells of sea cucumber Apostichopus japonicus - Shasha Wang; Yingqiu Zheng; Muyan Chen; Kenneth B. Storey (Journal of Oceanology and Limnology, 2021)

De novo transcriptome analysis of stressed blood clam (Anadara broughtonii) and identification of genes associated with hemoglobin - Yihang Wang; Shanshan Zhou; Tianyu Liu; Muyan Chen; Xiumei Zhang (Genes & Genomics, 2020)

The transcriptomic responses of the ark shell, Anadara broughtonii, to sulfide and hypoxia exposure - Yihang Wang; Shanshan Zhou; Tianyu Liu; Muyan Chen; Wentao Li; Xiumei Zhang (Molecular Biology Reports, 2019)

Comparison of intestinal microbiota and activities of digestive and immune-related enzymes of sea cucumber Apostichopus japonicus in two habitats - Qi Wang; Xiumei Zhang; Muyan Chen; Wentao Li; Peidong Zhang (Journal of Oceanology and Limnology, 2018)

Erratum to: Glycolytic regulation in aestivation of the sea cucumber Apostichopus japonicus: evidence from metabolite quantification and rate-limiting enzyme analyses - Xiaowei Xiang; Muyan Chen; Changwen Wu; Aiyi Zhu; Jingwen Yang; Zhenming Lv; Tianming Wang (Marine Biology, 2017)

Glycolytic regulation in aestivation of the sea cucumber Apostichopus japonicus: evidence from metabolite quantification and rate-limiting enzyme analyses - Xiaowei Xiang; Muyan Chen; Changwen Wu; Aiyi Zhu; Jingwen Yang; Zhenming Lv; Tianming Wang (Marine Biology, 2016)